ON THE IMPLEMENTATION OF HUMANITIES MODULES AT TECHNICAL UNIVERSITIES - Vladimir F. Gorokhov (Высшее образование в России)
The paper presents the review of the results of the International Conference "Humanities in Higher School: Theory, Practice, Implementation", which took place in November 2016 at the National Research Nuclear University (MEPhI), Moscow, under the support of Pon-tificia Universitas Gregoriana and University of Aosta Valley.